PERANAN PEMBELAJARAN GEOGRAFI DI SMA TERHADAP KESIAPSIAGAAN SISWA DALAM MENGHADAPI BENCANA BANJIR DI KABUPATEN SOLOK - Andini, Nisye Frisca (STKIP Pesisir Selatan, 2018)
This research aims to evaluate the role of geography learning in high school determined by the students' knowledge and awareness toward the risks of flood disaster in Kecamatan Kubung, West Sumatera. The students’ awareness and response are expected during the emergency condition of flood disaster, especially in securing their life and properties. The research was conducted in several high school in Kecamatan Kubung, Kabupaten Solok. The research use sample determination table (Isac and Michael) as the sampling technique, and multiple linear regression as the analysis method. The test results shows that there is a significant influence of knowledge and awareness toward the adolescent preparedness. The influence of both factors can be seen from the value of the determination coefficient that is equal to 0.757, which means the rate of high school students’ preparadness toward the risk of flood disaster in Kecamatan Kubung is 67.5%